2022
DOI: 10.1039/d2nj03555c
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the adsorption properties of a β-cyclodextrin/phillipsite organophilic composite for effective removal of toxic organophosphorus pesticides: kinetic and advanced equilibrium studies

Abstract: Natural phillipsite zeolite was functionalized with β-cyclodextrin chains and assessed as a potential organophilic and multifunctional adsorbent (CD/Ph) for three types of organophosphorus pesticides (Methyl parathion (MPn), omethoate (OM), and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…The observed behaviors are strongly correlated with the significant influence of pH on the MP ionization behaviors and the dominating charges on the outside surfaces of K, EXK, and β-CD/EXK . The chemically active groups of K, EXK, and β-CD/EXK were continuing to deprotonate as the alkaline levels of MP solutions escalated, and their outermost layers became totally saturated with negative electrical charges . Since the exteriors of K, EXK, and β-CD/EXK are dominated by negative charges, they act as centers for the electrostatic attractions for the positively charged soluble molecules of MP .…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…The observed behaviors are strongly correlated with the significant influence of pH on the MP ionization behaviors and the dominating charges on the outside surfaces of K, EXK, and β-CD/EXK . The chemically active groups of K, EXK, and β-CD/EXK were continuing to deprotonate as the alkaline levels of MP solutions escalated, and their outermost layers became totally saturated with negative electrical charges . Since the exteriors of K, EXK, and β-CD/EXK are dominated by negative charges, they act as centers for the electrostatic attractions for the positively charged soluble molecules of MP .…”
Section: Resultsmentioning
confidence: 90%
“…Finally, it has been observed that the third and last stages are predominant if K, EXK, and β-CD/EXK are in their equilibrium states of MP adsorption. This demonstrates that the sequestered MP molecules have fully filled or consumed all the existing effective binding sites (Figure B). , At this stage, MP adsorption is controlled by a number of processes, some of which may involve molecular interactions and/or interionic attraction mechanisms …”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The fundamental NiO/D and Ni@NiO/D chemical groups underwent substantial deprotonation reactions under alkaline conditions, leading to the formation of a large number of negative-charged hydroxyl ions across the exteriors of the blended particles. 11 Consequently, the alkaline situations maintain the charges of the exteriors of NiO/D and Ni@NiO/D particulates in a highly advantageous state with their negative surfaces, enabling them to strongly bind the positive AC insecticide via electrostatic forces. Additionally, an increase in pH levels significantly affects the production of OH groups.…”
Section: Resultsmentioning
confidence: 99%
“…8,9 Organophosphates (OPs) are extensively used as pesticides for crop protection owing to their notable performance and cost-effectiveness. 10,11 OP pesticides are commonly implemented to inhibit the activity of cholinesterase enzymes and minimize the proliferation of pests and weeds during the growth of crops such as rice, vegetables, cotton, and sorghum. 12,13 The chemical structures of such pesticides have significant toxicity and carcinogenic properties, particularly when they are present as soluble molecules inside both groundwater and surface water.…”
Section: Introductionmentioning
confidence: 99%